Study and Applications of an Unconditionally Stable Multi-Resolution Time-Domain Scheme - Cao, Qunsheng (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An unconditionally stable locally one-dimensional multi-resolution time-domain (LOD-MRTD) algorithm is studied, which is free of the Courant-Friedrich-Levy (CFL) stability condition. The LOD-MRTD method is reformulated to get more efficient and simple formulations. The unconditional stability and dispersion equations of the LOD-MRTD in two dimension (2D) case are analyzed, and a 2D example is calculated to demonstrate these characteristics.